Wakanda liberation is this? Interrogating Black Panther's relationship with colonialism. (2nd January 2020) - Ward, Jonathan
ABSTRACT: Ryan Coogler's Black Panther (2018) constitutes an intervention within representations of blackness within American culture. In a landscape in which the vast majority of depictions of black people in film remain severely limited and stereotypical, Coogler's blockbuster stands out as a celebration of blackness and a challenge of anti-black racism. The way in which the film grapples with the legacy of colonialism and represents an opportunity to deconstruct infrastructures of white supremacy as well as to engage with issues of black representation and marginalization more generally will be the primary focus of this article.